A light tunable differentiation system for the creation and control of consortia in yeast - Chetan Aditya (Nature Portfolio, 2021)
Artificial microbial consortia use division-of-labour to optimize production. Here the authors develop an optogenetic differentiation system in yeast to generate consortia from a single strain with tunable composition.